Counting the Oil Money and the Elderly : Norway's Public Sector Balance Sheet - Cabezon, Ezequiel (IMF Working Papers; Working Paper ;, 2018)
Based on a permanent income analysis, Gagnon (2018) has prominently suggested that Norway has saved too much, thereby free-riding on the rest of the world for demand. Our public sector balance sheet analysis comes to the opposite conclusion, chiefly because it also accounts for future aging costs. Unsurprisingly, we find that Norway's current assets exceed its liabilities by some 340 percent of mainland GDP. But its nonoil fiscal deficits have grown very large (to almost 8 percent of mainland GDP) and aging pressures are only commencing. Therefore, Norway's intertemporal financial net worth (IFNW) is negative, at about -240 percent of mainland GDP. As IFNW represents an intertemporal budget constraint, this implies that Norway's savings are likely insufficient to address aging costs without additional fiscal action.